Detail shop drawing of windows of 5th storey (RFA-028_Rev.A) - Arman Engineering Ltd. (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of both PDF and DWG version of drawings.